"A company of gentlemen": confederate veterans and southern universities. Issue 3 (1st September 2020) - Silkenat, David
ABSTRACT: Between 1911 and 1914, four major Southern public universities – the University of North Carolina, the University of Virginia, the University of Georgia, and the University of Alabama – conferred honorary degrees upon former students who had abandoned their studies to join the Confederate military. Some 400 Confederate veterans received this tribute a half century after their enlistment, during a critical moment in the development of Lost Cause commemoration, of Southern Progressivism, and of Southern higher education. This essay explores how the decision to honour former Confederates at these four state universities not only reflected the desire to recognize the patriotic sacrifices of aged Confederate veterans, but also helped to solidify a political order based on white supremacy and Progressive social reform.